Of the land - Law, Bryan (Filmmaker); Break Free Video (Firm); KITG Productions; Soundview Media Partners ([Toronto, Canada] : Break Free Video : KITG Productions, 2015)
Of the Land is a detailed exploration into our current food supply as well as a variety of organic options available to people who want to support sustainable farming methods.
Within the last half century, our agriculture and food has changed more than it has changed before in several thousand years. New technologies and scientific ingenuity have given rise to genetically modified organisms (GMO) and other novel foods. Some people have raised concerns about the safety of GMOs in our food supply, given their incredible dominance in the majority of our diet. Traditional, organic farmers, have consistently been under attack by large corporate farming interests, who seek to dominate the food industry and run family farms out of business. This film looks at our current food system as well as a variety of smaller, organic options available to consumers who want to support sustainable farming methods.
Originally released as a motion picture in 2015.
Chiefly live film footage, including selections from interviews, speeches, and conference presentations by scientists, policy experts, organic farmers, and activists; some archival film clips.
Cinematographer, Steven Davies ; editor, Bryan Law, Steven Davies ; music, Dan Dicks.
In English; with optional English subtitles.
Official selection, Phoenix Film Festival, 2015. Official selection, Cinema Verde Film Festival, 2015.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed August 30, 2017).
Keywords: Food supply -- Environmental aspects; Food supply -- Political aspects -- Canada; Genetically modified foods -- Health aspects; Genetically modified foods -- Environmental aspects; Genetically modified foods -- Political aspects -- Canada; Organic farming; Organic farming -- Ontario; Social action -- Ontario -- Case studies; Demonstrations -- Ontario -- Toronto; Food supply -- Political aspects -- United States; Genetically modified foods -- Political aspects -- United States; Organic farming -- Vermont; Social action -- Vermont -- Case studies; Demonstrations -- Washington (D.C.); Transgenic organisms; Food; Nonfiction films; Documentary films; Internet videos; Streaming video